Análise de metabólitos secundários em culturas de Pestalotiopsis sp e Aspergillus aculeatus - Rodrigues, Luis Henrique (2006)
Cariophylene sesquiterpenes are chemical compounds isolated from fungi of the Pestalotiopis genus in early studies developed in our research group. In the present work, a cultivation and analysis methodology were developed for these compounds in Pestalotiopsis, isolated from plants Pinus taeda, Swietenia macrophyla and Khaya invorenses. Different procedures were optimized for the extraction and analysis of the extracts employing liquid and gas chromatography coupled with mass spectrometry techniques (LC/MS and GC/MS). These studies had the intention of to detect the sesquiterpenes in fungal extracts without theys of isolation, and to check their production profile during a fixed cultivation period. The production of volatile organic compounds by the different species of Pestalotiospsis was also evaluated using hydrodestillation in Clevenger apparatus. The sesquiterpene cariophyllene was the main compound identified. Another study involving the secondary metabolites produced by Aspergillus aculeatus, a fungus isolated from the host plant Melia azedarach, was carried out. The target compounds in these studies were the dimeric aromatic poliketides Aurasperones A and B, Fonsesinones A and B, Orlandine and Kotanin. A poliketide production curve, obtained using HPLC, showed that the monomers are not detected during the early stage of development, indicating that probably the dimers are rapidly formed by the fungus or they are biosynthesized in the form already dimeric. Experiments of biotransformation showed that fungi possesss capacity to modify certain substracts, when cultivated in artificial ways.